2018
DOI: 10.2174/1874453201811010056
|View full text |Cite
|
Sign up to set email alerts
|

Different Messages are Transmitted by Individual Duet Contributions and Complete Duets in a Species with Highly Overlapped Duets

Abstract: Background: Duet function hypotheses have been mostly studied in bird species that produce duets with male and female solo songs. However, in order to understand if patterns of duet function are similar across all duetting species, it is highly necessary to test the duet function hypotheses in species that produce duets with vocalizations other than solo songs. Objective: We studied the responses of territorial pairs to each sex’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…White-eared Ground Sparrows (Melozone leucotis) show multi-functionality in duets. The response to playbacks of duets for this species showed an aggressive response to duets by the pair, indicating resource defence; however, depending on the sex, members of pairs would react more to same-sex signallers, indicating conflict functions (Sandoval et al, 2018). Yellow-breasted…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…White-eared Ground Sparrows (Melozone leucotis) show multi-functionality in duets. The response to playbacks of duets for this species showed an aggressive response to duets by the pair, indicating resource defence; however, depending on the sex, members of pairs would react more to same-sex signallers, indicating conflict functions (Sandoval et al, 2018). Yellow-breasted…”
Section: Discussionmentioning
confidence: 91%
“…White‐eared Ground Sparrows ( Melozone leucotis ) show multi‐functionality in duets. The response to playbacks of duets for this species showed an aggressive response to duets by the pair, indicating resource defence; however, depending on the sex, members of pairs would react more to same‐sex signallers, indicating conflict functions (Sandoval et al., 2018). Yellow‐breasted Boubous respond strongly towards duet and male solo playback, compared with female solo vocalisations, which can be interpreted as a way of male mate‐guarding behaviour.…”
Section: Discussionmentioning
confidence: 98%
“…Avian duets have been shown to perform a range of functions, including joint resource defense, mate defense, and pair coordination (Hall, 2009;Dahlin & Benedict, 2014). Work on the genera Melozone and Peucaea has demonstrated that duets of different species have similar functions in resource defense, providing a possible selective pressure maintaining this trait (Benedict, 2010;Sandoval, Méndez & Mennill, 2013;Illes, 2015;Sandoval, Juárez & Villarreal, 2018). Similarly, studies of other New World avian clades have shown that vocal duet presence and form are often evolutionarily conserved (Mann et al, 2009;Mitchell et al, 2019).…”
Section: Lability Versus Stability Of Behavioral and Morphological Traitsmentioning
confidence: 99%
“…Además, los patrones de actividad vocal pueden diferir entre especies, por ejemplo, mientras el tinamú ondulado (Crypturellus undulatus) es vocalmente más activo en el día; algunas aves como los bienparados (e.g., Nyctibius griseus y N. grandis) prefieren vocalizar más por las noches o madrugadas (Pérez-Granados & Schuchmann 2020). Otros escenarios nos acercan al entendimiento de conductas complejas de cooperación donde ambos sexos participan e interactúan para consolidar repertorios en duetos cumpliendo funciones en la defensa de territorios, recursos y pareja (Sandoval et al 2018). Ciertamente, la bioacústica nos permitirá seguir entendiendo los patrones de actividad vocal en aves, lo que a su vez nos proporcionará información necesaria para realizar estudios comparativos entre poblaciones y especies y que finalmente nos permitirá tener un mejor panorama sobre los orígenes de la diversidad vocal.…”
Section: Estado Del Arteunclassified